ChemInform Abstract: DBU‐Promoted Regioselective HBr‐Elimination of Vicinal Dibromides: Effects of the Adjacent Oxygen and/or Other Heterofunctional Groups. Issue 10 (March 2015) - Kutsumura, Noriki; Toguchi, Shohei; Iijima, Masatoshi; Tanaka, Osamu; Iwakura, Izumi; Saito, Takao
Abstract The HBr‐elimination of vicinal dibromides possessing an adjacent heteroatom is studied both experimentally and by theoretical calculations.